2010
DOI: 10.1074/jbc.m109.021824
|View full text |Cite
|
Sign up to set email alerts
|

Complex Regulation of the Transactivation Function of Hypoxia-inducible Factor-1α by Direct Interaction with Two Distinct Domains of the CREB-binding Protein/p300

Abstract: Activation of transcription in response to low oxygen tension is mediated by the hypoxia-inducible factor-1 (HIF-1). HIF-1 is a heterodimer of two proteins: aryl hydrocarbon receptor nuclear translocator and the oxygen-regulated HIF-1␣. The C-terminal activation domain of HIF-1␣ has been shown to interact with cysteine/ histidine-rich region 1 (CH1) of the coactivator CBP/p300 in a hypoxia-dependent manner. However, HIF forms lacking C-terminal activation domain (naturally occurring or genetically engineered) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
39
1
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(43 citation statements)
references
References 59 publications
2
39
1
1
Order By: Relevance
“…However, reduction of ARNT did not alter binding of USF2 and Pol II to the PAI1 promoter. Consistent with a reported role of HIF in recruiting CBP and p300 (5,81), hypoxic Hep3B/ARNT shRNA cells exhibited a noticeable reduction of CBP and p300 binding to the PAI1 promoter (Fig. 7A).…”
Section: Usf2supporting
confidence: 70%
See 1 more Smart Citation
“…However, reduction of ARNT did not alter binding of USF2 and Pol II to the PAI1 promoter. Consistent with a reported role of HIF in recruiting CBP and p300 (5,81), hypoxic Hep3B/ARNT shRNA cells exhibited a noticeable reduction of CBP and p300 binding to the PAI1 promoter (Fig. 7A).…”
Section: Usf2supporting
confidence: 70%
“…7A), indicating that USF2 is responsible for hypoxia-mediated increased CBP and p300 recruitment to the PAI1 promoter. HIF's role in activating HIF target genes was thought to be recruitment of CBP and p300 histone acetylases by C-terminal transactivation domains (C-TADs) as well as N-terminal TADs (N-TADs) of HIF1␣ and HIF2␣ (55,81). Thus, we conducted ChIP experiments in normoxic or hypoxic Hep3B/ARNT shRNA cells that have 80% ARNT reduction.…”
Section: Usf2mentioning
confidence: 99%
“…To further investigate the role of HIF-2a in b-catenin activation, we examined the possible involvement of p300 coactivator. It has been reported that the transcriptional activity of b-catenin is promoted by p300 (17) and that p300 is recruited by TADs of HIF-as (18,19). Therefore, we examined p300 recruitment by b-catenin, and found that the b-catenin-p300 binding was enhanced by full-length HIF-2a, but not by the d67 mutant (Fig.…”
Section: Hif-2a Activates B-catenin By Recruiting P300 Through Its Trmentioning
confidence: 98%
“…Because of the absence of an expected HIF-1␣-binding element in the region, it appeared that HIF-1␣ binding might be indirect. The transcription coactivator p300/CBP associates with HIF-1␣, as well as STAT3, in the formation of an active transcription complex for the transactivation of several genes (22,23). Therefore, we examined the association of p300/CBP in the complex.…”
Section: Binding Of Stat3 Hif-1␣ and P300/cbp To The Promoter Sitesmentioning
confidence: 99%